Modification of the Gelatin-Matrix Method for Enumeration of Respiring Bacterial Cells for Use with Salt-Marsh Water Samples - Newell, Steven Y. (1984)
In this report I describe a modification of the gelatin-matrix method for determining the percentages of bacterial cells having active electron transport systems. This modification is one-step fluorochroming followed by use of an antioxidant solution instead of the secondary gelatin layer. The modified technique is more successfully applicable to water samples containing high densities of flocculant particulate matter, owing to the brighter green fluorescence of the cells, which contrasts with the red-orange fluorescence of the floc.